Functional changes of Cys-loop receptors generated by electromagnetic fields - Tolosa, María Fernanda (2011)
Due to the rapid advances in communication technologies, the population is increasingly exposed to electromagnetic fields (EMFs). This has raised concern about potential health effects resulting from exposure to them. We here studied the influence of EMFs on AChR and 5HT3A receptors. We recorded macroscopic and single-channel currents from cells expressing these receptors and exposed to EMFs before or during agonist application. Exposure to EMFs (15 Hz-120 kHz) produces a significant decrease of the peak current, an increase on the rise time and no changes in the decay time constants of macroscopic currents activated by ACh. The peak current decreases as a function of EMF frequency (IC50 54 kHz). The effect on 5HT3A receptor currents is 3-fold more profound than on AChR currents, thus indicating different sensitivity of Cys-loop receptors to EMFs. The single-channel amplitude of AChR channels is not affected by the EMF, revealing that the reduction of macroscopic currents is originated from a change in the activation kinetics and not in the ion permeability of the receptor. In accordance with this, open time histograms change in EMF-exposed AChRs. Our results reveal that EMFs affect ligand-gated ion channel function and open doors to understand the mechanistic of such effect.